PENGARUH PEMBERIAN EKSTRAK ETANOL ALGA COKELAT (Sargassum sp.) TERHADAP HITUNG JENIS LEUKOSIT MENCIT (Mus musculus) PASCA DIINDUKSI STRES AKUT - Reski Toding Allo Lebang; Vina Z. Latuconsina; Halidah Rahawarin; Ingrid Hutagalung; Parningotan Y. Silalahi; Samuel Maruanaya (PAMERI, 2021)
Glucocorticoids are stress hormones that suppress normal immune responses by blocking Th1 cells. Glucocorticoids have an impact on decreasing the body's immune system and changes in leukocyte differentiation. Sargassum sp. is one type of brown algae that lives in the sea. Sargassum sp. contains metabolite compounds that are immunomodulatory. This study aims to determine the number of types of leukocytes in mice that are induced by stress and given ethanol extract of Sargassum sp. Pure experimental research design with post test only control group design. Thirty mice were divided into five treatment groups, namely the normal control group (KN), negative control (K-), positive control (K +), ethanol extract of Sargassum sp. 35% (P1) and 70% (P2). At K-, K +, P1 and P2 were given stress treatment with the FST (Forced Swim Test) method to see immobility time in mice. The treatment was given for seven days and on the 8th day the intracardial mice were taken. Observation of leukocytes from the blood smear of mice was carried out using a microscope with 1000x magnification. Observation data were analyzed by ANOVA. The results showed that the P1 group could reduce the percentage of neutrophils and monocytes but increase the percentage of lymphocytes, while the P2 group showed a decrease in the percentage of neutrophils, an increase in the percentage of lymphocytes, but could not decrease the percentage of monocytes compared to P1. The mean percentage of eosinophils and basophils did not change significantly, both in the treatment group and in the control group. However, statistical data shows no significant change between groups. So it can be concluded that stress treatment given to mice does not have a significant effect on the average percentage of monocytes, lymphocytes, neutrophils, eosinophils and basophils after being induced by stress.